Enhanced solar hydrogen generation using Cu–Cu2O integrated polypyrrole nanofibers as heterostructured catalysts. (28th February 2020) - Ghosh, Srabanti; Keshri, Shweta Rani; Bera, Susmita; Basu, Rajendra N.
Abstract: Nanostructured conducting polymeric materials are beneficial for electron conduction and mass transport, showing high photocatalytic performance under visible light. Herein, we report a colloidal synthesis of copper and copper oxides (Cu2 O) modified polypyrrole nanofibers (PPy) heterostructures, which demonstrates significantly high photocatalytic H2 generation under visible light. The presence of Cu nanoparticles (NPs) of 50 nm and cubic shaped Cu2 O nanoparticles of size 200 nm endows the heterostructures with a large specific surface area as well as good dispersion of nanoparticles on PPy nanofibers allows the migration of electron during catalysis. Cu2 O/PPy exhibits excellent H2 production (67 mmol h −1 ) which is 12 times higher than pure PPy (5.7 mmol h −1 ). The high catalytic activity of Cu2 O/PPy heterostructure provides a fervent alternative to noble metal-based catalysts for the hydrogen generation and water splitting. Graphical abstract: Image 1 Highlights: Cu and Cu2 O nanomaterials are used as a co-catalyst with PPy nanofibers. Cu2 O/PPy heterostructures able to generate hydrogen and oxygen under visible light. The obtained heterostructures exhibited excellent photoelectrochemical activity and stability. A p-n junction formed between p-type PPy and n-type Cu2 O which promotes charge-carrier separation efficiency.